The consumer’s choice among television displays: A multinomial logit approach (2013)
The consumer’s choice over a bundle of products depends on the observable and unobservable characteristics of the product and the consumer. The choice is made over the basis of maximizing utility subject to their income restrictions and, at the same time, firms make product differentiation decisions over the basis of maximizing profit. Quality is one way to differentiate products. An example of this type of differentiation happens in the TV market where several displays are developed. Our objective is to determine the probability for a consumer of choosing a type of display among five kinds: standard tube, LCD, plasma, projection and LED. Using a multinomial logit, we find that electronic appliances such as DVDs and audio systems, as well as socioeconomic status, increase the probability of choosing a high-tech display television. Our empirical approximation contributes to the further understanding of consumer rational behavior through the theory utility maximization and highlights the importance of studying the market structure and analyzing changes in welfare and efficiency